Creating (Socially-Distanced) Community in a Multi-site, Multi-disciplinary Department - Christina M. Wolfe (Academic Chairpersons Conference Proceedings, 2022)
In this presentation, I discuss ways to facilitate a sense of community in a multidisciplinary department at a multisite community college in a time of social distancing.
Keywords: academic leadership; communication; community; departmental culture; multidisciplinary department; multiple sites